EVALUASI IMPLEMENTASI PELATIHAN PENGAWASAN KESEHATAN LINGKUNGAN BAGI SANITARIAN PUSKESMAS DI PROVINSI RIAU - Irma Mariana; Jufenti Ade Fitri; Riski Novera Yenita; Eva Mayasari (Pelantar Press, 2026)
According to primary data from the UPT Bapelkes of the Riau Provincial Health Office in 2024 regarding the results of environmental health quality monitoring training for environmental sanitation workers at Community Health Centers, the average pre-test results for 20 participants were 55.6, which is still far below the graduation target of 80. This type of research uses a quantitative approach with a case study design conducted from March to July 2025. The population was 72 people, consisting of several community health centers in Riau Province. In this study, the sample was 20 (twenty-one) Environmental Sanitation Workers who participated in the training. Data analysis using descriptive analysis techniques was carried out through the calculation of frequency distribution, percentage, average value (mean) and standard deviation of each variable studied. Based on the results of the univariate analysis that has been done, it is known that all subjects amounted to 20 people in the female gender (80%) with the latest education of SI (50%). There is an influence of Environmental Health Quality Supervision Training for Environmental Sanitation Workers at the Community Health Center on the competence and performance of environmental sanitation workers, providing a positive impact. It is recommended that the UPT Bapelkes of the Riau Provincial Health Office can hold further training that is more specific and based on field case studies, so that the material is more applicable